Produção e caracterização de agregados sintéticos utilizando resíduos do processo Bayer - LIRA, Rodolfo Augusto do Rosário (2021)
Solid waste generated by the mining and metallurgy industry has been attracting interest from other industries, especially the ceramic industry, which consumes a large portion of these materials. Bauxite residue, for example, can generate materials with interesting mechanical characteristics, especially for applications in the civil construction sector. Some researches indicate that its use as a constituent in the production of synthetic aggregates can be a way to reduce the large amount of waste that is generated by mining companies. Based on this assumption and aiming to attenuate the use of natural resources such as sand, gravel and pebbles that are used on a large scale, the objective of this work was to develop light synthetic aggregates using bauxite, sand and clay residues. The production and composition were based on previous works with difference in the amount of clay (25%) in order to analyze possible differences in physical properties in relation to other researches in which between 5 and 10% of clay were used in the composition of the aggregate. The starting materials (waste from the Bayer process, sand and clay) were processed in a rotating drum to form pellets and sintered in electric ovens at temperatures of 1200 and 1250°c with 3-hour hold. Aggregates were characterized to determine physical, morphological and chemical properties. In the physical analysis, the aggregates had apparent specific masses of 2.15 g/cm3 and 1.88 g/cm3 for temperatures of 1200 and 1250°C, respectively. In the X-ray diffraction results, major phases such as Quartz, Mullite and Hematite were identified. In the results of scanning electron microscopy, it was possible to identify the presence of the secondary mullite phase, which presents a structure that resembles needles. The presence of this phase is very important for these materials, giving it good mechanical properties. Therefore, the use of bauxite residues in the production of synthetic aggregates can bring great benefits for both the generating industry and the ceramic industry, and especially for the environment.